Metabarcoding-based characterization of soil nematode communities to assess soil health in viticulture - Rubén Blanco-Pérez; María de Toro; Sergio Álvarez-Ortega; Alícia Pou; Sara Sánchez-Moreno; Raquel Campos-Herrera (Ecological Indicators)
Agricultural practices profoundly impact soil health, yet the tools available to assess these effects remain limited and require further refinement. Soil nematodes are valuable bioindicators of agroecosystem health due to their role in nutrient cycling and sensitivity to environmental changes. While traditional soil community assessments have relied on morphology-based identification, advances in molecular techniques, such as high-throughput sequencing (HTS) metabarcoding, enable more comprehensive and fine-scale characterizations. This study evaluated how pest and soil management practices influence soil nematode communities in DOCa Rioja vineyards (Northern Spain). We hypothesized that organic viticulture and cover cropping would enhance nematode diversity, food web complexity, and soil health indicators compared to integrated pest management (IPM) and tillage practices. We applied HTS metabarcoding to test this, identifying 114 nematode taxa to assess nematode diversity, trophic composition, and network connectivity across 57 vineyards. We also calculated diversity metrics and nematode-based indices and analyzed key abiotic soil properties to explore their influence on nematode community structure. Our results show that organic viticulture significantly enhanced nematode diversity (P < 0.001), food web complexity, and ecological stability, as reflected in significantly higher (P < 0.01) Maturity Index (MI) and Structure Index (SI) values, along with lower (P < 0.01) Basal Index (BI) values. Additionally, organic vineyards exhibited greater network connectivity, indicating a more structured and resilient soil food web than IPM. In contrast, tillage and cover cropping had limited effects on nematode community structure and soil health indices, suggesting a weaker influence on nematode-mediated soil functions under the studied conditions. These findings underscore the benefits of organic viticulture in enhancing soil biodiversity and ecological stability, reinforcing the role of sustainable farming practices in maintaining soil health. Furthermore, this study highlights the potential of nematode DNA metabarcoding as a robust tool for soil health assessment, providing a comprehensive, fine-scale perspective on soil nematode communities across different management strategies.